Performance of Polymer Modified Fibre Reinforced High Strength Concrete - Chandra Shekhar, M.; Sudharshan Reddy, B.; V. Tanuja, D. (Journal of Neonatal Surgery, 2025)
The report outlines the findings of an experimental study on the properties of polymer-modified steel fiber-reinforced concrete. The investigation encompasses compressive, flexural, and shear strength, employing styrene-butadiene rubber latex as the polymer. The fiber volume ranges from 1% to 10% at 1% intervals by weight of cement, while the polymer content varies at 5%, 10%, and 15% by weight of cement. The water within the polymer is considered part of the total water content. The research delves into the impact of polymer and fibers on the workability and wet density of fresh concrete. Additionally, the influence of dry curing on various strengths of fiber-reinforced concrete is explored. Various physical properties, including dry density, crack width, are also investigated. The workability of fiber-reinforced concrete diminishes with increasing fiber content, while enhancements in strengths are observed compared to normal concrete. In essence, the study evaluates the performance of polymer-modified fiber-reinforced high-strength concrete..